Assessing the value of family safety networks in child protective services: Early findings from Minnesota. Issue 4 (6th March 2017) - Nelson‐Dusek, Stephanie; Idzelis Rothe, Monica; Roberts, Yvonne Humenay; Pecora, Peter J.
Abstract: The considerable number of families served continues to place systemic challenges on the child welfare system. Jurisdictions are turning to new strategies to increase family engagement in services and to leverage taxed or limited resources. Signs of Safety® is a strengths‐based and safety‐focused approach to child protection work that is grounded in partnership and collaboration. This exploratory pilot study with a referred participant sample used interviews with 26 parents and 32 safety network members to explore respondents' perceptions and use of a safety plan and safety network, core components of the Signs of Safety framework. Findings from this pilot investigation include insights about how safety plans and safety networks are established, how they function, and opportunities for enhancing their use with families with the goal of providing supports that increase the likelihood of continued safety for children after case closure. Preliminary results also suggest these tools may contribute to reduced re‐reports to child protection.